2004
DOI: 10.1021/ac0353536
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Generation by UV Irradiation for Sample Introduction with Atomic Spectrometry

Abstract: /npsi/ctrl?action=rtdoc&an=8896355&lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?action=rtdoc&an=8896355&lang=fr READ THESE TERMS AND CONDITIONS CAREFULLY BEFORE USING THIS WEBSITE.http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
127
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(131 citation statements)
references
References 30 publications
3
127
1
Order By: Relevance
“…In the past years, photo-induced reduction or CVG was reported as a technique for remediation of heavy metal contamination [16][17][18][19]. This chemical vapour generation, in presence of organic acid under UV irradiation, was also coupled with atomic spectrometry for the analysis of selenium, mercury and other metal or non-metal element [20,21], which proved that the green, simple and selective UV-CVG is a useful new alternative to the conventional KBH 4 system. Further, a UV/nano-TiO 2 vapour generation device with formic acid was adopted for coupling HPLC with ICP-MS for the determination of inorganic Se(IV) and Se(VI) [22].…”
Section: Introductionmentioning
confidence: 97%
“…In the past years, photo-induced reduction or CVG was reported as a technique for remediation of heavy metal contamination [16][17][18][19]. This chemical vapour generation, in presence of organic acid under UV irradiation, was also coupled with atomic spectrometry for the analysis of selenium, mercury and other metal or non-metal element [20,21], which proved that the green, simple and selective UV-CVG is a useful new alternative to the conventional KBH 4 system. Further, a UV/nano-TiO 2 vapour generation device with formic acid was adopted for coupling HPLC with ICP-MS for the determination of inorganic Se(IV) and Se(VI) [22].…”
Section: Introductionmentioning
confidence: 97%
“…Guo et al [41] first introduced PVG in 2003, and applications of this new sample introduction quickly expanded [42,43]. A wide range of elements can be photochemically derivatized to volatile species, such as Hg [44,45], Ni [46,47], Se [43], Co [48,49], Fe [50], and I [51,52].…”
Section: Photochemical Vapor Generation Systemsmentioning
confidence: 99%
“…While, Bendl et al [14] suggested reducing species CH 2 CO generated in the photo-reduction process according to (2).…”
Section: Mechanism Of Photo-induced Chemical Vapour Generationmentioning
confidence: 99%
“…Photo-induced chemical vapour generation (CVG), introduced by Guo et al [1,2] is a new alternative sample introduction technique to traditional chemical vapour generation [3,4]. In this novel sample introduction method, volatile species were generated under UV irradiation with low molecular weight organic acid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation